AUDIT TATA KELOLA SISTEM INFORMASI APLIKASI SHOPEE MENGGUNAKAN FRAMEWORK COBIT 5 - Ripal Muhamad; Zahra Nur H, Karolina Astuti, Muhammad Fadhli, Riza Fahlapi (ADISAM PUBLISHER, 2024)
In the current digital era, information technology has become the backbone of business operations and strategy. Shopee, as one of the largest e-commerce platforms in Southeast Asia, relies heavily on a complex information system to carry out various business functions. This study aims to audit the information system governance of the Shopee application using the COBIT 5 framework. By utilizing the Monitor, Evaluate, Assess (MEA) domain of COBIT 5, this study evaluates the performance, compliance, and internal IT control systems at Shopee. Data was collected through online questionnaires distributed via WhatsApp groups to Shopee users. The audit results show that MEA01 and MEA02 are at the